The evolution of local stress during deformation twinning in a Mg-Gd-Y-Zn alloy. (1st January 2022) - Jia, Yong; Jiang, Shaosong; Tan, Jun; Lu, Zhen; Jiang, Jufu; Wang, Xiaojun
Abstract: In this study, we perform in-situ tensile testing and high-resolution electron backscatter diffraction (HR-EBSD) to monitor the twin local stresses at different stages: (i) before twinning, (ii) twins that have propagated into the parent crystal, and (iii) thickening of the twin lamella. The resolved shear stress (RSS) at the twin interface is calculated during deformation twinning, which indicates that the RSS evolution is a dynamic process. Negative shear stress is observed during the propagation stage, which provides evidence for the twinning shear transformation-induced stress reversal. Furthermore, a local Schmid factor (LSF) is used to evaluate the extent to which the local stress is dominated by the RSS on the identified twin plane. The experimental results indicate that the LSFs evolve with strain and are at their maximum level before twinning. The initiated twins are correlated with the highest LSFs compared with the unactivated variants. In addition, the product of the Luster Morris m ′ value times the LSF of the twin variant may reveal a threshold for the slip-induced twinning process. Graphical abstract: Image, graphical abstract